The Development of 3DPageflip Service System to Improve Performance Customer Services in Bank - Roki Juniadi; Indri Astuti; Fadillah Fadillah (STKIP Singkawang, 2019)
This study aims to produce a 3Dpageflip service system design in the learning of customer service material, the final product of a 3Dpageflip service system to improve Customer Service performance, through learning activities using a 3Dpageflip service system is expected to help skilled Customer Service in serving customer satisfaction at the Bank. This research is a research on the development of a 3Dpageflip service system by using the Borg and Gall development stage, and the subject of the research is Customer Service. The design of the model is developed using the ADDIE model. From the results of the media expert validation and expert service model validation, and Customer Service questionnaires about the 3Dpageflip service design system, the 3Dpageflip service system is well used in learning customer service material at the Bank. The results showed that the average response value of 83.92 3Dpageflip service system meant that it was well received, tested and feasible to use in the material of the customer service system in improving Customer Service performance.